Analisis Penerapan Pengendalian Biaya Lansung dan Biaya Tidak Langsung pada PT Natamas Plast - Nafia, Nabila; Viendyasari, Mila; Rahmawati, Devie (Jurnal EMT KITA, 2026)
This paper discusses the implementation of direct and indirect cost control procedures at PT Natamas Plast, particularly in managing operational expenses. It highlights the important roles of direct costs, such as raw materials and labor, as well as indirect costs, such as utilities and maintenance, in supporting production efficiency and effectiveness. The study also describes the advantages, disadvantages, challenges, and solutions adopted by the company in managing both types of costs. Using a descriptive qualitative approach, the research was conducted through field observations, interviews, documentation, and literature studies based on financial data and the company’s cost administration system. The results indicate that direct cost control has been carried out quite effectively, while indirect cost management still faces challenges, especially in resource efficiency. With more consistent supervision and budget evaluation, the company’s cost control can be further improved to support sustainability and overall performance.